PENGEMBANGAN E-MODUL BAHASA INGGRIS MENGGUNAKAN FLIPP BOOK MAKER (FBM) UNTUK MAHASISWA SEMESTER 1 PROGRAM STUDI HUKUM EKONOMI SYARI’AH STIF SYEIKH NAWAWI TANARA, SERANG - Kholid, Kholid (STAI Darul Qalam Tangerang, 2021)
This study aims to measure the effectiveness of developing an e-module (digital module) using the flipbook maker application to increase the understanding of Syari'ah Economic Law (HES) students at the Sheikh Nawawi Tanara School of Fiqh (STIF) towards English lecture material. In addition, this research activity is also carried out in order to provide input to the needs of aspects of language and English competence that are integrated with the study program that students take. This research is qualitative research (qualitative research) using a survey method through the google form facility in order to make it easier for researchers to get feedback on survey results. The results of the study show that 2 (two) things are the focus of attention, namely: 1) Regarding linguistic aspects, data can be obtained that 85.7% of students need material related to English expressions with competence. The language that students want is speaking skills that are integrated with terms, themes and narratives related to banking and sharia economics. 2) Modules in digital form (e-modules) are in great demand by students because they are very easy to operate via android, tablets, and laptops so that they are suitable for the world of students who can hardly be separated from android devices, tablets, and laptops and students can easily understand the material in the e-module because additional features can be added such as audio, video, image and so on to support understanding the material